2020
DOI: 10.46481/jnsps.2020.69
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed Collocation Method For Solving Singular Multi-order Fractional Differential Equations of Lane-Emden Type

Abstract: In this work, a general class of multi-order fractional differential equations of Lane-Emden type is considered. Here, an assumed approximate solution is substituted into a slightly perturbed form of the general class and the resulting equation is collocated at equally spaced interior points to give a system of linear algebraic equations which are then solved by suitable computer software; Maple 18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…x 0 (x − t) y(t)dt+ We solve this problem at N = 4 and 5, however, make use of N = 4 for demonstration. Integral form of example 2 is x Exact N = 4 N = 5 0.2 -0.6400000000e-2 -0.6400000000e-2 -0.6400000000e-2 0.4 -0.3840000000e-1 -0.3840000000e-1 -0.3840000000e-1 0.6 -0.864000000e-1 -0.8640000000e-1 -0.8640000000e-1 0.8 -0.1024000000 -0.1024000000 -0.1024000000 1.0 -0.9000000000e-3 -0.900000000e-3 -0.900000000e-3 Using approximate solution (4) on (18) gives…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…x 0 (x − t) y(t)dt+ We solve this problem at N = 4 and 5, however, make use of N = 4 for demonstration. Integral form of example 2 is x Exact N = 4 N = 5 0.2 -0.6400000000e-2 -0.6400000000e-2 -0.6400000000e-2 0.4 -0.3840000000e-1 -0.3840000000e-1 -0.3840000000e-1 0.6 -0.864000000e-1 -0.8640000000e-1 -0.8640000000e-1 0.8 -0.1024000000 -0.1024000000 -0.1024000000 1.0 -0.9000000000e-3 -0.900000000e-3 -0.900000000e-3 Using approximate solution (4) on (18) gives…”
Section: Examplementioning
confidence: 99%
“…Many different approaches have been adopted to investigate the solution of fractional integrodifferential equations, such as Adomian decompositions method [3][4][5], collocation method [6,7], Laplace decomposition method [8,9], Taylor expansion method [10], Least square method [9], differential transform method [11], homotopy perturbation method [12][13][14][15][16][17][18], sinc-collocation method [15][16][17] and variational iteration method [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[1]. Some of the numerical solution of fractional differential equations developed in the literature include: Perturbed collocation method [2], Adomian decompositions method by [3][4][5], Collocation method by [6][7][8][9], Chebyshev-Gelerkin method [10], Bernoulli matrix method [11], Differential transform method [12], Pseudospectral method [13], Bernstein Polynomials method [14,15], the Mellin transform approach [16]. [17] utilized a numerical approach based on the boubaker polynomial to generate approximate numerical solutions to the multi-order fractional differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained showed that the technique has the capacity to yield good results with less computational time and memory space. Using Perturbed Collocation Method (PCM) [12] solved Singular Multi-order Fractional Differential Equations (SMFDE) of Lane-Emden Type with results which converged to the exact solutions. Akbari-Ganji Method (AGM) was used by [13], [14], [15] and [16] to find the numerical solution of differential equations arising from different physical problems.…”
Section: Introductionmentioning
confidence: 99%